Answer

Verified

339k+ views

**Hint:**In this question, we have a trigonometric expression, which values find out. First, we simplify this expression in the form of a double angle and triple angle (trigonometric formula). Then we use the double angle and triple angle formula and solve it. After that, we convert them into quadratic equations. Then we find the roots of the quadratic equation. After that, we find the value of the given trigonometric expression.

**Complete step by step solution:**

In this question, we use the words double angle, triple angle. First, we know about the double angle formula.

Double angle formula: the double angle is called because they have a double angle of trigonometric functions like \[\sin 2\theta,\;\cos 2\theta \], etc.

The double angle formula is written as below in the form of\[\sin \].

\[ \Rightarrow \sin 2\theta = 2\sin \theta \cos \theta \]

Now we know about the triple angle formula.

Triple angle formula: the triple angle is called because they have a triple angle of trigonometric functions like \[\sin 3\theta,\;\cos 3\theta \], etc. the triple angle formula is written as below in the form of\[\sin \].

\[ \Rightarrow \sin 3\theta = 3\sin \theta - 4{\sin ^3}\theta \]

Now we come to the question. In the question, the trigonometric expression is given as below.

\[ \Rightarrow \sin \left( {\dfrac{\pi }{5}} \right)\]

Let we assume that,

\[ \Rightarrow \theta = \dfrac{\pi }{5}\]

Then,

\[5\theta = \pi \]

It can be written as below.

\[ \Rightarrow 3\theta = \pi - 2\theta \]

We write both sides of the trigonometric function\[\sin \].

Then,

\[ \Rightarrow \sin 3\theta = \sin \left( {\pi - 2\theta } \right)\]

We know that\[\sin \left( {\pi - \theta } \right) = \sin \theta \].

Then, the above expression is written as.

\[\sin 3\theta = \sin 2\theta \]

Now we use the double angle and triple angle formula.

Then,

\[ \Rightarrow 3\sin \theta - 4{\sin ^3}\theta = 2\sin \theta \cos \theta \]

We divided both sides with\[\sin \theta \].

Then,

\[ \Rightarrow 3 - 4{\sin ^2}\theta = 2\cos \theta \]

We know that\[{\sin ^2}\theta = 1 - {\cos ^2}\theta \].

Then the above expression is written as.

\[ \Rightarrow 3 - 4\left( {1 - {{\cos }^2}\theta } \right) = 2\cos \theta \]

Now we solve the above expression.

\[3 - 4 + 4{\cos ^2}\theta = 2\cos \theta \]

\[ \Rightarrow - 1 + 4{\cos ^2}\theta - 2\cos \theta = 0\]

We arrange the above expression as.

\[ \Rightarrow 4{\cos ^2}\theta - 2\cos \theta - 1 = 0\]

It is a quadratic equation. Hence the root of the quadratic equation is.

\[ \Rightarrow x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}\]

Then from the above quadratic equation, the root is

\[\cos \theta = \dfrac{{2 \pm \sqrt {{2^2} - 4 \times 4 \times \left( { - 1} \right)} }}{{2 \times 4}}\]

\[ \Rightarrow \cos \theta = \dfrac{{2 \pm \sqrt {4 + 16} }}{8}\]

\[ \Rightarrow \cos \theta = \dfrac{{1 \pm \sqrt 5 }}{4}\]

We know that \[\cos \theta \] cannot take negative value, then

\[ \Rightarrow \cos \theta = \dfrac{{1 + \sqrt 5 }}{4}\]

Then we find the value of\[\sin \theta \].

\[ \Rightarrow \sin \theta = \sqrt {1 - {{\cos }^2}\theta } \]

Put the \[\cos \theta \]from above.

Then,

\[ \Rightarrow \sin \theta = \sqrt {1 - {{\left( {\dfrac{{1 + \sqrt 5 }}{4}} \right)}^2}} \]

\[ \Rightarrow \sin \theta = \sqrt {1 - \left( {\dfrac{{1 + 5 + 2\sqrt 5 }}{{16}}} \right)} \]

\[\therefore \sin \theta = \dfrac{{\sqrt {10 - 2\sqrt 5 } }}{4}\]

Put the value of \[\theta \] in the above.

Then,

\[\sin \dfrac{\pi }{5} = \dfrac{{\sqrt {10 - 2\sqrt 5 } }}{4}\]

**Therefore, the value of \[\sin \dfrac{\pi }{5}\] is \[\dfrac{{\sqrt {10 - 2\sqrt 5 } }}{4}\].**

**Note:**

If you have a trigonometric function. And you want to find the value of that function. Then you can convert that function into double angle triple angle format. After applying the double angle and triple angle formula you can find the value of a trigonometric function.

Recently Updated Pages

Three beakers labelled as A B and C each containing 25 mL of water were taken A small amount of NaOH anhydrous CuSO4 and NaCl were added to the beakers A B and C respectively It was observed that there was an increase in the temperature of the solutions contained in beakers A and B whereas in case of beaker C the temperature of the solution falls Which one of the following statements isarecorrect i In beakers A and B exothermic process has occurred ii In beakers A and B endothermic process has occurred iii In beaker C exothermic process has occurred iv In beaker C endothermic process has occurred

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Define absolute refractive index of a medium

Find out what do the algal bloom and redtides sign class 10 biology CBSE

Prove that the function fleft x right xn is continuous class 12 maths CBSE

Find the values of other five trigonometric functions class 10 maths CBSE

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Difference Between Plant Cell and Animal Cell

Which places in India experience sunrise first and class 9 social science CBSE

The list which includes subjects of national importance class 10 social science CBSE

What is pollution? How many types of pollution? Define it

State the laws of reflection of light